La0.6Sr0.4Co0.2Fe0.8O3-d Hollow Fibre Membrane Performance Improvement by Coating of Ba0.5Sr0.5Co0.9Nb0.1O3-d Porous Layer - Han, D.; Wu, J.; Yan, Z.; Zhang, K.; Liu, Jian; Liu, Shaomin (Royal Society of Chemistry, 2014)
The oxygen permeation performance of perovskite La0.6Sr0.4Co0.2Fe0.8O3d (LSCF) hollow fibremembranes was enhanced by surface modification via coating of a Ba0.5Sr0.5Co0.9Nb0.1O3d (BSCN) porous layer. The hollow fibres were characterized by XRD, SEM and EDS elemental mapping and tested for air separation. Experimental results revealed that the BSCN porous layer had significantly improved the oxygen permeation flux of the coated LSCF hollow fibre membranes. Operated at 950 C and under the oxygen pressure gradient of the air/sweep gas, the maximum oxygen permeation flux of 1.92 mL cm2 min1 was achieved after the hollow fibre membrane was coated by a BSCN porous layer on both outer and inner surfaces. In addition, the modified membrane showed high oxygen permeation stability under the investigated operational conditions.